The concordance of swelling/tenderness with ultrasound-detected inflammatory lesions in patients with psoriatic arthritis - Sun, Xiaoying; Geng, Yan; Song, Zhibo; Deng, Xuerong; Hu, Xinyi; Wang, Yu; Zhang, Xiaohui; Zhao, Juan; Li, Guangtao; Ji, Lanlan; Xie, Wenhui; Huang, Hong; et al. (Frontiers in Immunology, 2025)
BackgroundPsoriatic arthritis (PsA) is a complex and varied inflammatory condition that can cause arthritis, enthesitis, dactylitis, and spondylitis. In recent years, ultrasound (US) imaging has emerged as a valuable adjunct to physical examination (PE) in the assessment of PsA. This study aims to assess the concordance between clinical manifestations of swelling/tenderness and US-detected inflammatory lesions in the wrists and hands of patients with PsA.MethodsThe study utilized the PKUPsA cohort and included both clinical and US evaluations of 30 joints per PsA patient, encompassing bilateral wrists, proximal interphalangeal (PIP), metacarpophalangeal (MCP), and distal interphalangeal (DIP) joints. Clinical assessments included the detection of tenderness or swelling, while US evaluations identified synovitis, tenosynovitis/paratenonitis, enthesitis, and soft tissue inflammation. Cohen’s kappa (κ) statistic was employed to measure the concordance between clinical and sonographic findings.ResultsA total of 188 patients with PsA were included in the study. US-detected inflammatory lesions were more common in swollen joints than tender joints (50.6% vs. 40.3%, p<0.01). The overall concordance between clinical findings and US-detected inflammatory lesions was found to be moderate (κ=0.448, p<0.01). Joint swelling showed a higher level of concordance with US-detected inflammation (κ=0.497, p<0.01) than tenderness (κ=0.406, p<0.01). In the MCPs and wrists, synovitis exhibited a higher concordance with PE than tenosynovitis/paratenonitis. In contrast, in most PIP joints, US-detected tenosynovitis/paratenonitis aligned more closely with PE than synovitis. In DIP joints, enthesitis showed a greater concordance with PE than both synovitis and tenosynovitis/paratenonitis.ConclusionsUltrasound-detected inflammatory lesions in PsA patients showed a moderate level of concordance with PE in PsA patients, but significant discrepancies were observed across different joints and lesion types. These findings highlight the importance of incorporating US into the routine management for a more comprehensive understanding of PsA.